Analisis Strategi Komunikasi Interpersonal dalam Meningkatkan Efektivitas Kepemimpinan di Lingkungan Organisasi Kampus - Adhi Kusuma; Sapanah Dana Niroh; Zidan Syarul (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Campus organizations are a strategic forum for developing student leadership, not only from a technical aspect, but also in terms of effective interpersonal communication. Leadership in a college environment has its own complexity because it involves individuals with diverse academic backgrounds, maturity levels, and goals. This study aims to understand the role of interpersonal communication in supporting leadership effectiveness in student organizations, especially in the Scout organization at UIN SMH Banten. Interpersonal communication that is two-way, inclusive, and empathetic can increase group cohesiveness, member participation, and the effectiveness of work program implementation. Strategies such as active listening, the use of adaptive communication media, and a relational approach to leadership have been shown to contribute to creating a democratic and productive organizational atmosphere. In addition, challenges such as miscommunication can be overcome through a systematic information documentation system